ASEI-PDSI Lesson Approach and Quality Assurance in Classroom Delivery in Ilorin West Local Government Area Basic Schools, Kwara State. - Muritala, A. Tukur; Omosidi, Abdulrahman S.; Awodiji, Omotayo A.; Olagunju, Oluwaseun. C. (International Journal of Educational Management, 2022)
Strengthening Mathematics, Arts and Science Education SMASE in-service Training initiatives aim at building a technologically inclined citizens and moving teaching and learning from the teacher-centered to student-centered. This study therefore assessed the attitude of basic school teachers to SMASE’S ASEI-PDSI lesson plan approach in the teaching and learning, the level of quality assurance in classroom delivery in basic schools and learners’ perception in the use of ASEI-PDSI lesson approach. A descriptive survey of expo facto research design was adopted. The population comprises all upper basic schools in Ilorin West Local Government, Kwara State. Purposively, principal officers, teachers and their students are the target population for the study. Simple random sampling procedure was used to select participants (100 teachers, 30 principal officers and 200 learners/students). “Teachers’ Attitude ASEI-PDSI Lesson Plan Questionnaire” (TAALPQ), “Principal Officers’ Quality Assurance in Classroom Delivery Checklist” (POQACD) and “Learners’ Perception of ASEI-PDSI Lesson Approach Checklist” (LPALAC) were used for data collection. Content and face validity of the instruments was done. The instruments were found reliable at 0.799, 0,815 and 0.628 coefficients respectively with the use of Cronbach Alpha. Descriptive statistics and inferential statistic of independent t-test were used. The hypothesis formulated was tested at 0.05 level of significance. It was found that teachers’ attitude towards ASEI-PDSI lesson plan approach was very good at 64 %, the level of quality assurance in the classroom delivery was moderate at 66.7 % and learners’ perception of the use of ASEI-PDSI lesson approach was outstandin at .0 %. Male teachers have more favorable attitude towards ASEI-PDSI lesson plan approach than the female teachers = (30.46; 28.36), t (2.026) = .042 ρ >.05. Hence, it was recommended that local and multi-national organisation support can be annexed to enhance the full implementation of this project via sponsorship and funding.